MicroRNA‐214‐3p enhances erastin‐induced ferroptosis by targeting ATF4 in hepatoma cells. Issue 7 (21st January 2020) - Bai, Tao; Liang, Ruopeng; Zhu, Rongtao; Wang, Weijie; Zhou, Lin; Sun, Yuling
Abstract: Primary liver cancer is the second most frequent cause of cancer‐related deaths. Ferroptosis, a recognized form of regulated cell death, recently gains attention. MicroRNA‐214‐3p (miR‐214) plays a regulatory role in hepatocarcinogenesis. However, the role of miR‐214 in cellular ferroptosis is unclear. This study aimed at elucidating whether miR‐214 could regulate ferroptosis of liver cancer. In vitro, HepG2 and Hep3B cancer cells were treated with erastin, a ferroptosis inducer, and then erastin was demonstrated to suppress the cell viability. Moreover, pre‐miR‐214 overexpression caused that HepG2 and Hep3B cells were more susceptible to erastin, whereas anti‐miR‐214 sponge showed the opposite effect. Additionally, pre‐miR‐214 overexpression increased the malondialdehyde and reactive oxygen species levels, upregulated Fe 2+ concentration, and decreased glutathione levels in cancer cells exposed to erastin. Further, erastin enhanced the activation of transcription factor 4 (ATF4) in HepG2 and Hep3B cells, and pre‐miR‐214 overexpression inhibited ATF4 expression. The luciferase reporter data validated ATF4 as a direct target of miR‐214. Cancer cells transfected with ATF4 overexpression plasmid rendered lower susceptible to miR‐214‐induced ferroptotic death. In vivo, erastin significantly reduced the size and weight of xenografted tumors, and miR‐214 elevated the ferroptosis‐promoting effects of erastin and decreased ATF4 expression. In summary, our study demonstrates that the ferroptosis‐promoting effects of miR‐214 in hepatoma cells are attributed at least to its inhibitory effects on ATF4, which may provide a new target for therapy of hepatoma regarding ferroptosis. Abstract : In summary, our study demonstrates that the ferroptosis‐promoting effects of miR‐214 in hepatoma cells are attributed at least to its inhibitory effects on activation of transcription factor 4, which may provide a new target for therapy of hepatoma regarding ferroptosis.